P 27. VPS13D: One family, one mutation, two phenotypes. Issue 8 (August 2021) - Petry-Schmelzer, J.N.; Keller, N.; Karakaya, M.; Wirth, B.; Fink, G.R.; Wunderlich, G.
Abstract : Case Series. We report a 19-year-old male patient with a five-year history of a progressive gait impairment. Motor and cognitive development during childhood was normal. There were no neurologic diseases in family history besides the sister of the patient, reported to have a developmental delay but no physical impairment. On physical examination, the patient had a saccadic pursuit, gaze-evoked nystagmus, and mild hypophonia, accompanied by mild dysmetria in the lower limbs, spastic tetraparesis pronounced at the lower limbs, and a spastic ataxic gait with footdrop on the left. The sister (17 years) presented with a history of developmental delay and intellectual disability, first recognized at the age of 2-3 years. On examination, dysarthrophonia was prominent, whereas only mild cerebellar symptoms and mild tetraparesis without spasticity were detected. For further examinations we also refer to Table 1. Trio-exome sequencing revealed compound-heterozygous variants in VPS13D (p.Ser4117*, p.Gly4177Asp) in the male patient. The segregation analysis via Sanger sequencing showed the same compound heterozygous variants in the sister and confirmed the trans configuration in the parental samples. Discussion. Pathogenic variants in VPS13D have so far been reported in 12 families (23 patients). The most frequent symptoms described comprise cerebellar ataxia, additional movement disorders (dystonia, chorea and tremor), cognitive impairment, and spastic paraplegia. 1–3 Previous studies carefully hypothesized that the combination of missense and loss-of-function (LOF) variants tend to cause relatively pure ataxia and/or spasticity, whereas non-essential splice site/LOF variants or other combinations may be associated with a broader and more severe spectrum of phenotypes. 2 When considering that the siblings reported here had the same compound heterozygous variants in VPS13D but a very different phenotype, a specific phenotype-genotype correlation seems unlikely. This makes it even more important to be aware of this gene, especially in patients presenting with childhood-onset ataxia-plus syndrome or suspected hereditary spastic paraplegia. References 1. Gauthier J et al. Recessive mutations in VPS13D cause childhood onset movement disorders. Ann Neurol 2018 2. Seong E et al. Mutations in VPS13D lead to a new recessive ataxia with spasticity and mitochondrial defects. Ann Neurol 2018 3. Koh K et al. VPS13D-related disorders presenting as a pure and complicated form of hereditary spastic paraplegia. Mol Genet Genomic Med 2020 Table 1. Phenotype and clinical investications of the siblings.